2015
DOI: 10.18410/jebmh/2015/478
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity and Marital Quality Among Wives of Patients With Alcohol Dependence Syndrome

Abstract: BACKGROUND: Alcohol Dependence syndrome (ADS) is one of the most common psychiatric disorders that has deleterious consequences not only on the patient with ADS but also hampers social, financial, and legal matters of his family hence could be considered as a disorder of the family. Spouses of patients with ADS, a key member of such dysfunctional family system, are most vulnerable to have significant psychiatric disorders like adjustment disorders, mood disorders, anxiety disorders and psychosocial problems. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 14 publications
2
10
2
1
Order By: Relevance
“…It was observed in this study that diagnosis of anxiety was higher in spouses of alcoholic husbands (16%) as compared with those of nonalcoholic husbands (12%). These findings were in concordance with findings of Bagul et al 6 and Gohil et al 8 A prominent finding noticed in this study was that 18 (36%) spouses of alcohol-dependent men had depression, whereas in controls, it was seen in only 7 (14%) spouses. These findings were similar to the studies conducted in similar areas in different parts of the world.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was observed in this study that diagnosis of anxiety was higher in spouses of alcoholic husbands (16%) as compared with those of nonalcoholic husbands (12%). These findings were in concordance with findings of Bagul et al 6 and Gohil et al 8 A prominent finding noticed in this study was that 18 (36%) spouses of alcohol-dependent men had depression, whereas in controls, it was seen in only 7 (14%) spouses. These findings were similar to the studies conducted in similar areas in different parts of the world.…”
Section: Discussionsupporting
confidence: 93%
“…In similar studies, it was found that the majority of spouses of men with alcohol dependence syndrome were in the age group of 24 to 50 years, which was in concordance with our study. 3,5,6 In this study, it was also seen that the psychiatric morbidities among spouses of men with alcohol dependence were significantly higher in the cases as compared with controls. It was observed in studies conducted by Mammen et al 7 and Bagul et al 6 that prevalence of psychiatric morbidities in wives of men with alcohol dependence syndrome was similar.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Forty-one percent of the couples having their duration of marital life between 1 and 10 years and psychiatric morbidity were also present to be more among them constituting about 29.7%. This is in contrast to the study done from Maharashtra,[ 9 ] where they observed more of psychiatric illness in spouses married for more than 21 years and they got significant association between psychiatric morbidity of spouses with their duration of marital life; this may be lower number of couples in the group above 21 years of married life in this study. We did not observe any statistical significant difference between the groups.…”
Section: Discussioncontrasting
confidence: 99%